A FUNCTIONAL LINGUISTIC PERSPECTIVE ON DEVELOPING LANGUAGE - McCabe, Anne (Anne M.) (New York : Routledge, 2021)
"This volume offers a comprehensive account of language development from a systemic functional linguistic (SFL) perspective, integrating theory and data from a wide range of research studies"--
Includes bibliographical references and index.
Keywords: Language acquisition; Functionalism (Linguistics)